1993
DOI: 10.1111/j.1460-9568.1993.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

PDGF‐BB Exerts Trophic Activity on Cultured GABA Interneurons from the Newborn Rat Cerebellum

Abstract: Platelet-derived growth factor (PDGF) is a well known mitogen for mesenchyme-derived cells and glial cells. Its presence in neuronal cells of the central nervous system has only recently been described. We have shown earlier that neurons of newborn rat brains in culture express PDGF beta-receptors and that PDGF-BB, a homodimer of PDGF B-chain, increases survival and promotes neurite outgrowth of newborn cerebellar cells (Smits et al., Proc. Natl Acad. Sci. USA, 88, 8159-8163, 1991). In this study, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In the CA1 and CA3 areas of the rodent hippocampus, the relative postnatal growth of the comissural/associational terminal ®elds, and the elaboration of stratum radiatum pyramidal dendrites, are most rapid in the second postnatal week (Loy, 1980;Pokorny and Yamamoto, 1981). PDGF-B/c-SIS has been shown to exhibit various properties, including enhancement of neurite extension, induction of c-fos (Smits et al, 1993), stimulation of tyrosine phosphorylation (Cooper et al, 1982), inhibition of gapjunctional communication (Maldonado et al, 1988), and inhibition of NMDA receptor function (Valenzuela et al, 1996), all of which are consistent with the possible involvement of PDGF-B/c-SIS in synaptic transmission. Considering the abundant receptor (PDGFR-b) expression in neonatal neurons (Smits et al, 1991), the expression of PDGF-B/c-SIS in the hippocampus during the second postnatal week may be related to the maturation of neurons, including as neurite extension and elaboration of synaptic network.…”
Section: Discussionmentioning
confidence: 68%
“…In the CA1 and CA3 areas of the rodent hippocampus, the relative postnatal growth of the comissural/associational terminal ®elds, and the elaboration of stratum radiatum pyramidal dendrites, are most rapid in the second postnatal week (Loy, 1980;Pokorny and Yamamoto, 1981). PDGF-B/c-SIS has been shown to exhibit various properties, including enhancement of neurite extension, induction of c-fos (Smits et al, 1993), stimulation of tyrosine phosphorylation (Cooper et al, 1982), inhibition of gapjunctional communication (Maldonado et al, 1988), and inhibition of NMDA receptor function (Valenzuela et al, 1996), all of which are consistent with the possible involvement of PDGF-B/c-SIS in synaptic transmission. Considering the abundant receptor (PDGFR-b) expression in neonatal neurons (Smits et al, 1991), the expression of PDGF-B/c-SIS in the hippocampus during the second postnatal week may be related to the maturation of neurons, including as neurite extension and elaboration of synaptic network.…”
Section: Discussionmentioning
confidence: 68%
“…Here, we have analyzed the actions of a series of PDGF receptors in these cells in an effort to identify signals important for Na ϩ channel expression, a crucial aspect of neuronal differentiation. While PDGF receptors are expressed in many populations of neurons (14,55,64,68,69), they are not normally expressed in wildtype PC12 cells. Therefore, in this study, we took advantage of previously generated PC12 sublines that stably express PDGF receptors (79).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we took advantage of previously generated PC12 sublines that stably express PDGF receptors (79). Although there are no published estimates of the number of PDGF receptors in primary neurons for comparison, the levels of PDGF receptors in these PC12 sublines are such that PDGF elicits in them many of the same responses that it does in primary neurons, including increases in survival, c-fos induction, neurite outgrowth, and the induction of enzymes involved in neurotransmitter synthesis (55,68,69). Furthermore, in these sublines, PDGF mimics the actions of NGF in all responses examined so far, including the induction of Na ϩ channel expression and the activation of signaling molecules such as Ras, B-Raf, Raf-1, and MAPK to levels comparable to those observed in response to NGF (18,79).…”
Section: Discussionmentioning
confidence: 99%
“…PDGF, like the neurothrophins, is 1) produced locally and is important for the development, differentiation, proliferation, and survival of neuronal and glial cells (7,10,11,17); 2) coupled to tyrosine kinase receptors that activate complex intracellular signaling pathways (2); and 3) released as part of the compensatory response to central nervous system injury or disease (13,15,16). We now report that PDGF exerts another function that is characteristic of the neurotrophic factors, which is the modulation of neurotransmitter receptors in the central nervous system (29).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this elevation in PDGF levels is involved not only in the pathogenesis of these conditions but also in the tissue repair processes associated with these diseases. In this regard, it has been shown that PDGF exerts neurotrophic effects on GABAergic and dopaminergic neurons (17,18) and that it protects hip-pocampal neurons against energy deprivation and oxidative injury in vitro (19).…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%